2018
DOI: 10.1002/2017rg000568
|View full text |Cite
|
Sign up to set email alerts
|

ENSO Atmospheric Teleconnections and Their Response to Greenhouse Gas Forcing

Abstract: El Niño and Southern Oscillation (ENSO) is the most prominent year‐to‐year climate fluctuation on Earth, alternating between anomalously warm (El Niño) and cold (La Niña) sea surface temperature (SST) conditions in the tropical Pacific. ENSO exerts its impacts on remote regions of the globe through atmospheric teleconnections, affecting extreme weather events worldwide. However, these teleconnections are inherently nonlinear and sensitive to ENSO SST anomaly patterns and amplitudes. In addition, teleconnection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
295
2
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(354 citation statements)
references
References 193 publications
(340 reference statements)
21
295
2
3
Order By: Relevance
“…Overall, the result shown here indicates a more likely significant ENSO teleconnection on tropical IO and the IOD, especially regarding the western part of tropical IO, during the 2006–2100 period. The weak ENSO teleconnection found in several models might be due to the change of mean atmospheric circulation caused by anthropogenic forcing (Yeh et al, ). Other study (Ham et al, ) found that the weakening of ENSO‐IOD connection in recent decades (i.e., the 2000s and 2010s) is related to changes of ENSO spatial patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the result shown here indicates a more likely significant ENSO teleconnection on tropical IO and the IOD, especially regarding the western part of tropical IO, during the 2006–2100 period. The weak ENSO teleconnection found in several models might be due to the change of mean atmospheric circulation caused by anthropogenic forcing (Yeh et al, ). Other study (Ham et al, ) found that the weakening of ENSO‐IOD connection in recent decades (i.e., the 2000s and 2010s) is related to changes of ENSO spatial patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Our results confirm Yeh et al . () findings on the EN events of the 1982–2016 period, which they classified as of the EP (CP) type before (after) 1998. Indeed, the 1982–1997 and 1998–2016 periods overlap, respectively, the CAMO/WPDO and WAMO/CPDO mean states.…”
Section: Discussionmentioning
confidence: 99%
“…While climate anomalies in North America of similar general character are common during La Niña, the intensity of these anomalies was again highly unusual. A wide range of processes can potentially alter observed anomalies during any individual event, and therefore, these episodes do not provide a definitive basis for attributing changes in the strength of ENSO or its teleconnections, a challenge that relates to both the evaluation of events in nature (e.g., Seager et al, ; Yeh et al, ) and models (Deser et al, ; Guilyardi et al, ). They do, however, raise questions regarding the role a warming climate may have had on both these and even more recent ENSO‐related extremes in California (Swain et al, ; Williams et al, , ; Yoon, Wang, Gillies, Hipps, et al, ) and other regions (Herrera & Ault, ; Wang, Huang, et al, ; Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%